The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0252332
|View full text |Cite|
|
Sign up to set email alerts
|

Tracking COVID-19 vaccine hesitancy and logistical challenges: A machine learning approach

Abstract: In this study, we use an effective word embedding model (word2vec) to systematically track ’vaccine hesitancy’ and ’logistical challenges’ associated with the Covid-19 vaccines, in the USA. To that effect, we use news articles from reputed media sources and create dictionaries to estimate different aspects of vaccine hesitancy and logistical challenges. Using machine learning and natural language processing techniques, we have developed (i) three sub-dictionaries that indicate vaccine hesitancy, and (ii) anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…However, political disagreement over vaccines could be detrimental because they were often associated with vaccine hesitancy, reduced confidence in scientific and health facts [ 71 ], and decreased policy support for immunizations [ 72 ]. Recent research suggested that as different vaccines passed phase trials and were made available to the public, the discussions over vaccine efficacy and safety sharply increased in the United States [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, political disagreement over vaccines could be detrimental because they were often associated with vaccine hesitancy, reduced confidence in scientific and health facts [ 71 ], and decreased policy support for immunizations [ 72 ]. Recent research suggested that as different vaccines passed phase trials and were made available to the public, the discussions over vaccine efficacy and safety sharply increased in the United States [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…For reference, the entirety of the selected papers can be found in Table 1, and their citations are as follows: Ghanchi et al 2020a, b;Elkhouly et al 2020;Mulvey et al 2020;Sun et al 2020;Lu et al 2020;Beato-Víbora 2020;Mehra et al 2020a, b;Mehra et al 2020a, b;Walach et al 2021;Dutta et al 2021;Friedlich et al 2021;Ali et al 2020a, b;Lin 2021;Ali et al 2020a, b;Khalifa et al 2020;Gul et al 2021;Victor 2020a, b;Victor 2020a, b;Colchero et al 2021;Saha et al 2021;Ma et al 2021;Imran et al 2021;Akbar et al 2020;Ferdous et al 2021;Jiménez-Ruiz et al 2021;Savaris et al 2021;Grech 2020a, b;Zago Filho et al 2020;Atangana et al 2021;Mao et al 2021;Fioranelli et al 2020;Deokar et al 2020;Temmerman 2021;Ibrahimagić et al 2021;Saxena 2020;Grech 2020a, b;Din et al 2020;Bae et al 2020;Zeng et al 2020;Funck-Brentano et al 2020;Woodle et al 2021;…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have processed the text at multiple stages with the help of Spacy (version 2.3.5)— a free , open-source Natural Language Processing library for Python , Stanza (version 1.1.1), Gensim (version 3.8.3), and Regular Expression package (version 2020.11.13) toolkits [ 73 ]. We have briefly discussed these stages below:…”
Section: Methodsmentioning
confidence: 99%
“…Data pre-processing. In this study, we have processed the text at multiple stages with the help of Spacy (version 2.3.5)-a free, open-source Natural Language Processing library for Python, Stanza (version 1.1.1), Gensim (version 3.8.3), and Regular Expression package (version 2020.11.13) toolkits [73]. We have briefly discussed these stages below: a. Pre-processing sentences: Regex has been used to eliminate "E-mails, URLs, punctuations, new line characters, single characters, digits (i.e., numbers), and extra spaces" [22,74].…”
Section: Sample Collectionmentioning
confidence: 99%